Islam and government: an analytical review on Khumayni’s Kashf al-Asrār and Wilāyat al-Fāqih - Sudarnoto Abdul Hakim (Indonesian Journal of Islam and Muslim Societies, 2018)
This paper is an attempt to scrutinize Khumayni’s ideas especially on government as explained in his works Kashf al-Asrar, and Wilayat al-Faqih. While focusing on Khumayni’s ideas as the main issues of discussion, the paper tries to find the significance of the ideas for the Iranian revolution in 1979.The paper argues that the ideas on government were mainly triggered by the Reza Shah’s dictatorial, and secular government. It is not exaggerated to mention that according to Khumayni a new sytem of government based on Islamic ideology as a revolutionary system of government was needed in a sense that an Islamic government will implement justice. As will be discussed later, the idea of Islamic government as the single alternative was extensively supported by students, intelligentsias, urban peoples, poor peoples, and others.Artikel ini berusaha mendiskusikan pemikiran Imam Khumayni tentang pemerintah sebagaimana yang dijelaskan dalam karyanya Kasyf al-Asrar dan Wilayat Faqih. Sambil memberikan perhatian terhadap isu pokok, artikel ini ingin menggali kaitan kuat pemikiran Khumayni dengan revolusi Iran yang terjadi pada tahun 1979. Penulis berpandangan bahwa gagasan-gagasannya tentang pemerintah merupakan respons atau sikapnya terhadap kecenderungan pemerintahan diktatorial dan sekular Reza Shah. Tidak berlebihan untuk dinyatakan bahwa menurut Imam Khumayni sebuah pemerintahan Revolusioner yang didasarkan kepada Ideologi Islam sangat dibutuhkan karena pemerintahan Islam seperti inilah yang akan mampu menegakkan keadilan.Sebagaimana yang akan didiskusikan nanti ide pembentukan pemerintah inimemperoleh dukungan secara ekstensif antara lain dari mahasiswa, inteligensia,masyarakat kota dan orang-orang miskin.